Identificación de genes codificantes de enzimas que participan en la biosíntesis de compuestos nutracéuticos en la cianobacteria Anabaena sp., región Loreto - Gonzáles Arzubialdes, Rosana (2024)
Cyanobacteria, such as Anabaena sp., offer a promising alternative for producing high-value commercial nutraceutical compounds, such as polyphenols and carotenoids. DNA sequencing technology allows for identifying genes involved in the biosynthesis of these compounds in cyanobacteria. The main objective of this research, conducted between 2021 and 2022 at the Biotechnology and Bioenergy Laboratory of the Universidad Científica del Perú, was to identify the genes that encode enzymes involved in the biosynthesis of nutraceutical compounds in Anabaena sp. To achieve this objective, a methodology was implemented that included the cultivation of the cyanobacterium, genome sequencing and assembly, functional annotation, reconstruction of the biosynthetic pathways of polyphenols and carotenoids, and quantification of these compounds. As a result, the genome of Anabaena sp. was assembled, comprising 4.15 Mbp, and 2,849 genes that encode proteins were annotated. Subsequently, the biosynthetic pathways of polyphenols and carotenoids were reconstructed, identifying the involved genes and enzymes. Furthermore, the results revealed that Anabaena sp. produces significant amounts of polyphenols (0.72 ± 0.01 mg gallic acid equivalent/g dry biomass) and carotenoids (5.77 ± 0.30 µg/g dry biomass). These findings suggest that Anabaena sp. has great biotechnological potential for the production of nutraceutical compounds, opening opportunities for metabolic engineering and the development of new products with added value.